2018
DOI: 10.1016/j.jvir.2017.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Microwave versus Radiofrequency Ablation of Colorectal Liver Metastases: Ablation with Clear Margins (A0) Provides the Best Local Tumor Control

Abstract: Regardless of the thermal ablation modality used, margins larger than 5 mm are critical for local tumor control, with no LTP noted for margins over 10 mm. Unlike RF ablation, the efficiency of MW ablation was not affected for perivascular tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
201
5
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(223 citation statements)
references
References 33 publications
13
201
5
4
Order By: Relevance
“…Evidence suggests that metastases > 3 cm are more likely to undergo incomplete ablation. Local tumor progression-free survival after ablation in mutant-RAS was significantly worse than wild type [39][40][41][42]. Blood vessels > 3 mm may cause dispersion in tissue heating.…”
Section: Unfit Patients (Fig 1b)mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that metastases > 3 cm are more likely to undergo incomplete ablation. Local tumor progression-free survival after ablation in mutant-RAS was significantly worse than wild type [39][40][41][42]. Blood vessels > 3 mm may cause dispersion in tissue heating.…”
Section: Unfit Patients (Fig 1b)mentioning
confidence: 99%
“…Radiofrequency is the most commonly used thermal ablation therapy since the late 90s and has shown as much as 94% of local control and 31% 5-year OS when treated tumors are ≤ 3 cm, centrally located and with ablation margins greater than 5 mm [39]. MW is a promising technology with some advantages over RF [40]. The indications for RF and MW are well-located tumors less than 5 cm.…”
Section: Unfit Patients (Fig 1b)mentioning
confidence: 99%
“…It was previously reported that the biopsy proof of CTA and adequate safety margins (>5 mm) are independent predictors of LTP and yielded the best oncologic outcomes after resection or ablation . These factors were demonstrated to be associated with better local tumor control and a better survival rate after hepatic malignant tumor ablation for the existence of satellite focal or microscopic disease within 5 mm around the index tumor . Evidence showed that margins larger than 5 mm were critical for local tumor control, with no LTP noted for margins over 10 mm, regardless of the thermal ablation modality used, and MWA proved to be resilient to the heat‐sink effect compared to RFA, offering good control for perivascular tumors .…”
Section: Discussionmentioning
confidence: 98%
“…Theoretical benefits of MWA over RFA include larger ablation zone, shorter duration, and no heat‐sink effect . There are some studies reporting the outcomes of MWA for colorectal liver metastases as a safe and effective modality for use in the treatment of CRLM patients . Correa‐Gallego et al.…”
Section: Specific Techniques To Increase Resectabilitymentioning
confidence: 99%